2020
DOI: 10.1111/1462-2920.14945
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation strategies of soil rare and abundant microbial taxa in response to changing climatic regimes

Abstract: Summary Despite the important roles of soil microbes, especially the most diverse rare taxa in maintaining community diversity and multifunctionality, how different climate regimes alter the stability and functions of the rare microbial biosphere remains unknown. We reciprocally transplanted field soils across a latitudinal gradient to simulate climate change and sampled the soils annually after harvesting the maize over the following 6 years (from 2005 to 2011). By sequencing microbial 16S ribosomal RNA gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
108
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(115 citation statements)
references
References 57 publications
(82 reference statements)
6
108
1
Order By: Relevance
“…Therefore, the three top OTUs in our study will be critical drivers, or indicators, of key soil biogeochemical processes. Though rare soil bacteria are also the drivers of key functions in terrestrial ecosystems, which may be due to effects that are disproportionately large given their abundance or via the provision of insurance effects (Jousset et al, 2017), their roles in biogeochemical cycles is far less clear (Liang et al, 2020). Thus, it is critical that future research describes the contribution of rare soil bacteria driving ecosystem multifunctionality.…”
Section: The Contributions Of Krd Control To Soil Bacterial Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the three top OTUs in our study will be critical drivers, or indicators, of key soil biogeochemical processes. Though rare soil bacteria are also the drivers of key functions in terrestrial ecosystems, which may be due to effects that are disproportionately large given their abundance or via the provision of insurance effects (Jousset et al, 2017), their roles in biogeochemical cycles is far less clear (Liang et al, 2020). Thus, it is critical that future research describes the contribution of rare soil bacteria driving ecosystem multifunctionality.…”
Section: The Contributions Of Krd Control To Soil Bacterial Communitiesmentioning
confidence: 99%
“…Microorganisms are important components of soils (Beveridge, 1989), which play major roles in maintaining biogeochemical cycling, complexity and stability of belowground ecosystems (Delgado-Baquerizo et al, 2018Wagg et al, 2019). Predictive understanding of soil bacterial communities is very important to forecast the ecological consequences caused by environmental changes (Delgado-Baquerizo et al, 2018;Liang et al, 2020). Besides, the advent of high-throughput sequencing technologies provide a rapid and low-cost tool to understand microbial ecology, such as microbial community structures, diversities, interactions and co-occurrence patterns (Loman et al, 2012;Ma et al, 2016;Xue et al, 2017Xue et al, , 2020Schmidt et al, 2019;Wagg et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to a skewed abundance distribution in a local microbial community, with relatively few dominant and a large number of rare species (alternatively known as a "rare biosphere") [17,19,20]. Previous studies have reported that rare and abundant species often show different distribution patterns and functional traits [21][22][23]. Therefore, disentangling the biogeography and community assembly of rare and abundant microbial taxa is essential for understanding microbedriven ecosystem processes and functions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, local physicochemical properties have greater effects on both rare and abundant bacterial β-diversity compared to geospatial factors [20]. However, most studies investigate the biogeography of rare and abundant bacterial communities in agricultural soils [17,22,24,25], and little is known about rare and abundant bacterial and fungal taxa in natural wetlands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation